Drawing and Performing Exploration in Ruin Site (diségno, 2023)
Concept of ruin is changed today. Building mass becomes a tool for terrorization of the body, it is a structure for the community's memory, and building becomes a place where working as witness is revelatory. The representation of ruin has an important role which not only presents various unity between subject and mass but also creates non-contextualized dialog in which all subjects and their relation with the site is drawing various abstract presentations of the environment. This paper is based on the concept of ruin which comes to architectural design practice in history. The aim of this paper is to meet our ancestral colleague today’s experiment of ruin and ruining site at first find a contemporary model and perspective to evaluate this areal research. Drawing is not an analytic tool; drawing becomes a tool to progress the investigation on site what is not given by space in the moment. Drawing ruins offers special interaction with the 21st century where the world of crises becomes a chance to change the dynamic of life in terms of culture and aesthetics. As a result, what drawing ruins teaches us, as it did help with its sacred inspiration about form animation of architects, expands the form to use as a key in tying moments for developing alternatives of experiment in actual time. Drawing is a creation of an actual miracle against physical limits which is an experience kind of a censure.
Keywords: ruin; operation; time; aesthetic; Avant-garde